The Arctic Bear Whisperer : Finland as an Arctic Ambassador in 1986–1989 - Koskinen, Julia K. (Helsingin yliopisto, 2019)
During the Cold War, the Arctic became a stage for the superpowers’ rivalry. The more ballistical armament was developed further, the more the Arctic armament increased. In the 1980s, the Arctic region was a region where the Cold War’s escalation was a real fear. Simultaneously the environmental questions started to concern more and more. Furthermore, although international agreements to protect nature had been negotiated and bilateral ones were being accelerated, there was no organisation for the Arctic dealing region as a whole. This lack of cooperation encountered with détente, the US and the Soviet Union’s leaders converged with rhetoric about restrictions on armaments. When Gorbachev gave a speech on October 1987 in Murmansk and longed for further cooperation in the Arctic region, a situation arose, which enabled the opening of cooperation negotiations. Eventually, Finland was the first to seize the moment, and this led to Finland’s initiative. The initiative aimed to arrange a Conference on the Protection of the Environment in Finland. This master’s thesis examines Finland’s Arctic diplomacy from September 1986 to October 1989, from The Reykjavík Summit to when the first meeting of Arctic issues with eight Arctic states was kept. More precisely, this thesis research how Finland was performing Arctic diplomacy during the period and if there were a change to Finland’s line after the Gorbachev’s speech. Hence, the thesis examines what type of reactions and consequences Gorbachev’s Murmansk speech affected in Finland’s foreign policy. Moreover, this thesis is interested in who was conducting nascent cooperation in the Arctic Region. The primary data used in this thesis are Finland’s Foreign Minister’s archives documents. The study shows that Finland’s Arctic diplomacy was at first in 1986, observative and reactional. However, after Gorbachev’s speech in Murmansk, Finland took the lead and worked actively to start cooperation. In this role, Finland needed to act as a balancer between the Arctic countries’ ...